Effects of Trunk Motion, Touch, and Articulation on Upper-Limb Velocities and on Joint Contribution to Endpoint Velocities During the Production of Loud Piano Tones - Verdugo, Felipe; Pelletier, Justine; Michaud, Benjamin; Traube, Caroline; Begon, Mickaël (Frontiers in Psychology, 2020)
Piano performance involves several levels of motor abundancy. Identification of kinematic strategies that enhance performance and reduce risks of practice-related musculoskeletal disorders (PRMD) represents an important research topic since more than half of professional pianists might suffer from PRMD during their career. Studies in biomechanics have highlighted the benefits of using proximal upper-limb joints to reduce the load on distal segments by effectively creating velocity and force at the finger-key interaction. If scientific research has documented postural and expressive features of pianists’ trunk motion, there is currently a lack of scientific evidence assessing the role of trunk motion in sound-production and in injury prevention. We address this gap by integrating motion of the pelvis and thorax in the analysis of both upper-limb linear velocities and joint angular contribution to endpoint velocities. Specifically, this study aims to assess kinematic features of different types of touch and articulation and the impact of trunk motion on these features. Twelve pianists performed repetitive loud and slow-paced keystrokes. They were asked to vary: i) body implication (use of trunk and upper limb motion or use of only upper limb motion), ii) touch (struck touch, initiating the attack with the fingertip at a certain distance from the key surface, or pressed touch, initiating the attack with the fingertip in contact with the key surface), and iii) articulation (staccato, short finger-key contact time, or tenuto, sustained finger-key contact time). Data were collected using a 3D motion capture system and a sound recording device. Results show that body implication, touch, and articulation modified kinematic features of loud keystrokes, which exhibited not only downward but also important forward segmental velocities (particularly in pressed touch and staccato articulation). Pelvic anterior rotation had a prominent role in the production of loud tones as it effectively contributed to create forward linear velocities at the upper limb. The reported findings have implications for performance, teaching and research domains since they provide evidence of how pianists’ trunk motion can actively contribute to the sound-production and might not only be associated with either postural or expressive features.